SEROLOGICAL DETECTION OF COXIELLA BURNETII CHRONIC INFECTION- PHASE 1 IN SERUM OF HUMAN AND SHEEP AT AL-QADISIYAH PROVINCE, IRAQ - Mithal Kareem Abass Al-Hassani (Al-Qadisiyah Journal of Pure Science, 2019)
The present study was carried out to estimate the prevalence of chronic infections with C. burnetii in humans and sheep at different regions in Al-Qadisiyah province/Iraq, using specific-species enzyme-linked immunosorbent assay (ELISA) kits. An overall 366 blood samples, 182 human and 184 sheep, were collected aseptically during the period of February/2018 to November/2018. Total prevalence of C. burnetii phase-1 was 7.38% sero-positive samples that comprising 3.3% humans and 11.41% sheep. Regarding to residence factor, significant elevation (P<0.05) in sero-positive results among rural areas were recorded in both human (7.94%) and sheep (15%) samples. Data concerning to age factor were detected on significant increases (P<0.05) in sero-positive results of humans having an age of >30 years (3.42%), and in sheep having an age of >24 months (27.08%). Among sex factor, significant increases (P<0.05) in sero-positive prevalence of chronic infections were seen in samples of male human (6.56%) and female sheep (12.84%).